FORMACIÓN DE SUJETOS DE DERECHO DESDE LA TEORÍA CRÍTICA Y ÁMBITO JURÍDICO (2016)
In the course of a conceptual synthesis article on training for the exercise of human rights developed from the perspective of critical theory and analysis of their support from some authors; the same as the product of an experience in which the incidence of power relations in the development of law is analyzed participation in children of Basic Education Primary. It contains the analysis of some statements that have failed with the intention of guaranteeing the right to education, due process, free development of personality of students who take the standard and legal instruments seeking the restitution of the right ; failures oriented processes to be followed against the different cases of school discipline.Article concepts defined by the Court with respect to the right to education, Student Handbook, due process, right to free development of personality relate. He concludes by emphasizing the importance of recognizing the human being as a subject of rights, developed under interpersonal relationships characterized by horizontality of power linking dialogue, participation and ultimately democracy.